Visual evoked potentials in response to flashes in the cat cortex (Revista Española de Fisiología, 1994)
A model is presented of visually evoked potentials (VEPs) in the cerebral cortex of cats after binocular stimulation by means of flashes. The VEPs consist of four components: P1, N1, P2 and N2 which appear during the first 100 ms after the stimulation is produced. This model has been found in all the animals used in the experiments and is repeated with small variations at almost all the recording points. After studying the data obtained, a hypothesis is put forward for the possible origin of the four components in the primary visual area.